The synergy of activity-based costing (ABC) and the theory of constraints (TOC) in environmental cost management - Asriani Ningsih; Hasnur Sahati; Syamsul Ratu Loly; F. E. Daromes (Indonesia Accounting Research Journal, 2025)
This study aims to examine the integration of Activity-Based Costing (ABC) and the Theory of Constraints (TOC) as a conceptual framework for developing environmentally conscious and efficient environmental cost management. A systematic literature review was conducted on twenty relevant scientific publications to identify key patterns, findings, and integration opportunities between the two approaches. The results indicate that ABC enhances the accuracy of environmental cost information by tracing activity-based sources of energy waste, emissions, and waste generation, while TOC focuses on identifying and managing systemic constraints that limit efficiency and sustainability in production processes. The integration of ABC and TOC provides a comprehensive environmental cost management framework that goes beyond economic efficiency and strengthens organizational awareness of ecological limits. Conceptually, this synergy contributes to the advancement of environmental accounting as a knowledge-based system that links economic value with ecological responsibility and offers future development potential through digital technologies such as big data analytics, the Internet of Things (IoT), and artificial intelligence–based environmental management.